Measuring Deprivations in the Slums of Bangladesh : Implications for Achieving Sustainable Development Goals - Patel, Amit; Joseph, George; Shrestha, Anne; Foint, Yaeli (Taylor and Francis, 2019)
Approximately 880 million people, or one in four urban residents, live in slums today. While this enumeration is useful, it is not a trivial exercise to estimate slum population for a city, let alone globally, especially when the definition of a slum remains a debatable construct. To demonstrate this point empirically, we utilize a household survey from nine cities in Bangladesh and provide three different estimates of slum population based on three distinct definitions. We use a contextual definition that was adapted by the Government of Bangladesh, and two universal definitions that were adapted by the international development community. Two of the universal definitions were proposed to track progress on the Millennium Development Goals and the Sustainable Development Goals, respectively. By applying these different definitions to the same data, we found that the Bangladeshi Government’s definition provides slum population estimates that are far lower compared to those when we apply the definitions provided by the international development community. Such underestimation could misguide policymakers who want to know the extent of the policy problem, influence what kind of policy solutions will be pursued, and directly affect how these solutions will be targeted to respective populations.